Leptospirosis and Pancreatitis Complication - Diany N Taher; Murdani Abdullah; Marcellus Simadibrata; Herdiman T Pohan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2005)
Leptospirosis is a wide-spread zoonosis in the world, especially in the tropical countries. Ninety percent of cases are characterized by abrupt fever and have good prognosis, but in 10% of cases, exacerbation will occur and the mortality rate is about 10%. Leptospirosis may strike the entire organ, including gastrointestinal tract. Pancreatitis in leptospira is characterized by increased serum amylase levels, with mean values of five times normal. Early diagnosis and prompt treatment will engender good prognosis. Treatment of acute pancreatitis caused by leptospira is similar with other acute pancreatitis treatment caused by other agents. The pathophysiology of leptospira infection includes endotoxin, hemolysis and lipase. Keywords: Leptospirosis, pancreatitis, diagnosis